What journalism tells us about memory, mind and media. (17th December 2022) - Zelizer, Barbie
Abstract: This article looks to journalism in order to understand the relationship between memory, mind and media more fully. Using the urgency that characterises the current news environment as a reflection of broader information flows, the article considers journalism's embrace of complex time to address the demands of speed. It suggests that the temporal practices adopted by both individual journalists and the journalistic community offer a model for institutions wrestling with the ontological uncertainty generated by current times, providing mechanisms to navigate and even offset the unending demands of simultaneity, immediacy and instantaneity.